Comparative evaluation between the genotypic and phenotypic methods for detection of drug-resistant Mycobacterium tuberculosis - Salim , Saira; Shah, Syed Asim Ali; Asim, Fareena; Anwar, Saba; Shoukat, Aniqa; Iqbal, Naila (Infectious Diseases Journal of Pakistan, 2025)
Background: Tuberculosis (TB) is one of the major health problems with significant morbidity and mortality worldwide. According to world health organization in 2020 published guidelines for diagnosis and treatment of TB. To compare between genotypic and phenotypic methods for detection of drug resistant Mycobacterium tuberculosis. Material and Methods: This cross-sectional validation study was conducted from January to September 2024 in BSL-3 laboratories of Islamabad Diagnostic Center, Izzat Ali Shah Hospital, and POF Hospital Wah Cantt, Pakistan. A total of 87 culture-positive Mycobacterium tuberculosis (MTB) isolates were tested for susceptibility to Rifampicin, Isoniazid, Ethambutol, and Streptomycin using the MGIT 960 system and GeneXpert. DNA was extracted with the Gentra System kit, and multiplex PCR targeting rpoB, katG, and embB genes was performed. Gel electrophoresis was used to compare banding patterns of MDR and XDR MTB. Results: Out of 87 MTB samples 4 were multidrug resistant (MDR) and 30 were Single drug resistant (SDR). Among single drug resistant 2 were Rifampicin resistant, 24 were isoniazid resistant ,3 were ethambutol resistant. 3 samples use control (negative, positive and normal) non-MTB samples. and 50 samples were detected as MOTTS, The Sensitivity, Specificity, PPV, NPV and DA of MDR, Rifampicin, Isoniazid and Ethambutol were66.67%, 100.00%,33.33%, 71.43%,66.67%, 100.00%, 100.00%, 50.00%, 75.00%,85.71%,80.00%,96.00%, 50.00%,84.50%, ,100.00%, 50.00%,75.00%, 100.00%and 80.00% respectively genotypically by (multiplex PCR). Conclusion; In this study genotypic methods for detection of drug resistant MTB were rapid as compare to phenotypic methods for timely and active management. Keywords: Genotypic, Mycobacterium tuberculosis, Phenotypic.